CHARACTERIZATION OF LITHIC COMPLEXES FROM BUIA (DANDIERO BASIN, DANAKIL DEPRESSION, ERITREA) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2004)
This paper discusses a very partial sampling of the archeological evidence found in more than 200 sites containing lithic artefacts and faunal remains which have been surveyed in the Dandiero (Buia) Basin (Danakil Depression, Eritrea). All the lithic complexes are referred to the Acheulean. The authors present the results of  a preliminary study carried on some of the most important assemblages, especially the complex referred to the Homo-bearing levels. The lithic assemblages are characterized by different frequencies of hand-axes, cleavers, choppers and flakes. The techno-typological characters of the artefacts, all of which coform to an Acheulean standard, allow us to propose some preliminary hypotheses about their variability. The analyzed assemblages are then compared to the Early Paleolithic lithic complexes in east Africa.